Effector γδ T cells in human renal fibrosis and chronic kidney disease. Issue 1 (20th April 2018) - Law, Becker Meng-Po; Wilkinson, Ray; Wang, Xiangju; Kildey, Katrina; Lindner, Mae; Beagley, Kenneth; Healy, Helen; Kassianos, Andrew J
ABSTRACT: Background: γδ T cells are effector lymphocytes recognized as key players during chronic inflammatory processes. Mouse studies suggest a pathological role for γδ T cells in models of kidney disease. Here we evaluated γδ T cells in human native kidneys with tubulointerstitial fibrosis, the pathological hallmark of chronic kidney disease. Methods: γδ T cells were extracted from human kidney tissue and enumerated and phenotyped by multicolour flow cytometry. Localization and cytokine production by γδ T cells was examined by immunofluorescent microscopy. Results: We detected significantly elevated numbers of γδ T cells in diseased biopsies with tubulointerstitial fibrosis compared with diseased biopsies without fibrosis and healthy kidney tissue. At a subset level, only numbers of Vδ1 + γδ T cells were significantly elevated in fibrotic kidney tissue. Expression levels of cluster of differentiation 161 (CD161), a marker of human memory T cells with potential for innate-like function and interleukin (IL)-17A production, were significantly elevated on γδ T cells from fibrotic biopsies compared with nonfibrotic kidney tissue. Flow cytometric characterization of CD161 + γδ T cells in fibrotic biopsies revealed significantly elevated expression of natural killer (NK) cell–associated markers CD56, CD16 and CD336 (NKp44) compared with CD161 − γδ T cells, indicative of a cytotoxic phenotype. Immunofluorescent analysis of fibrotic kidney tissue localized the accumulation of γδ T cells within the tubulointerstitium, with γδ T cells identified, for the first time, as a source of pro-inflammatory cytokine IL-17A. Conclusions: Collectively, our data suggest that human effector γδ T cells contribute to the fibrotic process and thus progression to chronic kidney disease.